The Effect of CEO Personal Characteristics on CEO Overconfidence in Doing Earnings Management in Manufacturing Companies in Indonesia - Tysna Dyah Ayu Pramesti; Endang Sri Andayani; Sri Pujiningsih (CV ODIS, 2022)
The purpose of this research is to test Upper Echelons Theory by researching the relationship between CEO overconfidence and decisions in Earnings management. This research also identifies whether monitoring from external parties, especially institutional shareholdings, plays an important role in moderating Earnings management decisions concerning the behavior of overconfident CEOs. The author uses the measurement of the CEO's characteristics based on age, education level, and work experience, while overconfidence is measured based on the CEO's portfolio decisions. The sample consists of 68 manufacturing companies listed on the Indonesia Stock Exchange from 2017-2019. The results showed that age and work experience did not affect CEO overconfidence, while education level had an effect. Furthermore, the CEO's characteristics (age, education level, and work experience), through overconfidence, do not affect Earnings management. Other results also show that overconfidence does not affect Earnings management. The moderating effect of institutional share ownership has no effect on CEO overconfidence in Earnings management. The results of this research can provide benefits for users of financial information, namely internal parties (management), as a material consideration in the selection of a CEO. As for external parties (government, investors/potential investors, and creditors/prospective creditors), it can be used as a performance appraisal as well as a basis for decision-making.